7-3x=5x+19

Simple and best practice solution for 7-3x=5x+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-3x=5x+19 equation:


Simplifying
7 + -3x = 5x + 19

Reorder the terms:
7 + -3x = 19 + 5x

Solving
7 + -3x = 19 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
7 + -3x + -5x = 19 + 5x + -5x

Combine like terms: -3x + -5x = -8x
7 + -8x = 19 + 5x + -5x

Combine like terms: 5x + -5x = 0
7 + -8x = 19 + 0
7 + -8x = 19

Add '-7' to each side of the equation.
7 + -7 + -8x = 19 + -7

Combine like terms: 7 + -7 = 0
0 + -8x = 19 + -7
-8x = 19 + -7

Combine like terms: 19 + -7 = 12
-8x = 12

Divide each side by '-8'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 5p-7=4p+3 | | 4m-5=6m+d | | (2x+1)+y=56 | | 16-3p=-21 | | 110+(3x-20)=180 | | 4x+12+34=180 | | 9x-8y=16 | | x^3-5x^2+2x+10=0 | | x^3-5x+2x^2+10=0 | | x^3-15=39 | | 12+x-x^2= | | 20-x-x^2= | | 14-5x-x^2= | | 9(x-4)+2(1+4x)=0 | | 12+4x-x^2= | | 2a-10=-8 | | 5-4x-x^2= | | -5(-3-x)-12=3(1+11x) | | 4x+7=6x-2 | | -11+8x=5x+7 | | 2x-45=15 | | -4x+-3(x-5)=8x | | 8+2x-x^2= | | 8x-9=8(x-1)+1 | | 2x-21x+20=0 | | 5+6d=10+1d | | 64.00+x=67.68 | | 10(x+7)=10(x+11) | | 10x-7=10x-7 | | (3x+7)+(3x-5)=0 | | 2(x-3.00)=10.80 | | 10x+y=53 |

Equations solver categories